Brain metastases from primary tumors, vol 2 : epidemiology, biology, and therapy - Hayat, M. A., 1940- (Elsevier, 2015)
With an annual rate of more than 12 million global diagnoses and 7.6 million deaths, the societal and economic burden of cancer cannot be overstated. Brain metastases are the most common malignant tumors of the central nervous system, yet their incidence appears to be increasing in spite of the advancement of cancer therapies. While much is known about primary cancers (including primary brain tumors), less work has been done to uncover the roots of metastatic disease. This volume fills that gap, serving as the first reference to focus primarily on the link between primary cancers and brain. Source other than Library of Congress
ncludes bibliographical references and index
Keywords: Brain -- Tumors; Brain metastasis; Brain Neoplasms -- surgery